ANALISIS PRIORITAS PENANGANAN BANJIR KALI KONTO, PROVINSI JAWA TIMUR - Dian Indrawati; Mohammad Bagus Adityawan; Diki Maulana Ichsan; Dhemi Harlan; Joko Nugroho (Rekayasa Sipil, 2022)
Flood in Kali Konto is a disastrous hazard which strikes a lot of housing, infrastructures and paddy fields along its river banks almost every year. In 2021, along with destroyed revertment at roolagh 70 area, flood inundated more than 10 villages in Kabupaten Jombang and several more in Malang and Kediri. However, flood management at Kali Konto needs special consideration because several conditions, include watershed area pattern, extremely slope condition changing, numerous materials from Kelud mountain eruption in several part of Konto river, and a lot of infrastructures which laid in Konto river. This paper discussed about appropriate infrastructures which derived from hydrology and hydraulics modeling for Q2 and Q50 flood return periods. Since the model resulted 49 locations, Analytical Hierarchy Process (AHP) model used for determining priority for scaling down flood hazard in Kali Konto. The most priority comes to Karang Tengah, Blaru and Bugasur Kedaleman area based on the most losses occurred.